TINJAUAN YURIDIS TERHADAP PENYALAHGUNAAN KEWENANGAN DALAM PENANGGUHAN PENAHANAN - Cahyadi, Rizal (Jurnal HUKUM BISNIS, 2026)
Suspension of detention is a right stipulated in the Indonesian criminal law system, which serves as protection for suspects or defendants undergoing legal proceedings. However, in practice, this authority is often abused by law enforcement officials. Abuse of authority in suspending detention can result in a failure to realize the principle of justice that should be received by all parties involved in the criminal justice system. This research is a normative legal study using an approach that focuses on statutes (statute approach) and relevant legal concepts (conceptual approach). Keywords: Abuse of authority, suspension of detention, criminal law